Answer:
![\frac{5x+2}{3x^2+4x-4}= \frac{2}{3x-2}+\frac{1}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B5x%2B2%7D%7B3x%5E2%2B4x-4%7D%3D%20%5Cfrac%7B2%7D%7B3x-2%7D%2B%5Cfrac%7B1%7D%7Bx%2B2%7D)
Step-by-step explanation:
Ooook, step 1: write the denominator as a product, or we're not going anywhere. Can't spot any two factor by staring at it, so quadratic formula it is.
![x= \frac13(-2 \pm \sqrt{4+12})=\frac13(-2\pm4) = -2;\frac23](https://tex.z-dn.net/?f=x%3D%20%5Cfrac13%28-2%20%5Cpm%20%5Csqrt%7B4%2B12%7D%29%3D%5Cfrac13%28-2%5Cpm4%29%20%3D%20-2%3B%5Cfrac23)
We got our toots, let's split the denominator now: ![3x^2+4x-4 = (3x-2)(x+2)\\](https://tex.z-dn.net/?f=3x%5E2%2B4x-4%20%3D%20%283x-2%29%28x%2B2%29%5C%5C)
Now it's all a matter of writing down what we need:
![\frac{5x-2}{3x^2+4x-4}=\frac{5x-2}{(3x-2)(x+2)} = \frac{A}{3x-2}+\frac{B}{x+2} = \frac{A(x+2)+B(3x-2)}{(3x-2)(x+2)}=\frac{Ax+2A+3Bx-2B}{(3x-2)(x+2)} =\frac{(A+3B)x+(2A-2B)}{(3x-2)(x+2)}](https://tex.z-dn.net/?f=%5Cfrac%7B5x-2%7D%7B3x%5E2%2B4x-4%7D%3D%5Cfrac%7B5x-2%7D%7B%283x-2%29%28x%2B2%29%7D%20%3D%20%5Cfrac%7BA%7D%7B3x-2%7D%2B%5Cfrac%7BB%7D%7Bx%2B2%7D%20%3D%20%5Cfrac%7BA%28x%2B2%29%2BB%283x-2%29%7D%7B%283x-2%29%28x%2B2%29%7D%3D%5Cfrac%7BAx%2B2A%2B3Bx-2B%7D%7B%283x-2%29%28x%2B2%29%7D%20%3D%5Cfrac%7B%28A%2B3B%29x%2B%282A-2B%29%7D%7B%283x-2%29%28x%2B2%29%7D)
Here comes the fun part. Two ways: the fast and loose, and the long one.
<u>Fast and loose</u>: let's look only at the numerators of the 3rd to last and first step:
If we plugged a convenient value, let's say
the coeffcent of A would disappear, and we would be able to find B. Let's do it. ![A(-2+2) + B(3(-2)-2) = 5(-2)+2 \rightarrow -8B =-8 B=1](https://tex.z-dn.net/?f=A%28-2%2B2%29%20%2B%20B%283%28-2%29-2%29%20%3D%205%28-2%29%2B2%20%5Crightarrow%20-8B%20%3D-8%20B%3D1)
At this point we have B, let's pick a different value of x, let's say 1, to get A:
![A(3) + 1(1) = 7 \rightarrow 3A=6 \rightarrow A=2](https://tex.z-dn.net/?f=A%283%29%20%2B%201%281%29%20%3D%207%20%5Crightarrow%203A%3D6%20%5Crightarrow%20A%3D2)
<u>More traditional: </u>Pick the first and last numerators:
. Stare at them long enough and pick your favourite excuse to justify the following system (two polynomials are equal if the coefficents are equal, polynomials create a vector space of base ![(1,x,x^2...)](https://tex.z-dn.net/?f=%281%2Cx%2Cx%5E2...%29)
![\left \{ {A+3B=5} \atop {2A-2B=2}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7BA%2B3B%3D5%7D%20%5Catop%20%7B2A-2B%3D2%7D%7D%20%5Cright.)
Again,
is a solution.
Either way, the solution is:
![\frac{5x+2}{3x^2+4x-4}= \frac{2}{3x-2}+\frac{1}{x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B5x%2B2%7D%7B3x%5E2%2B4x-4%7D%3D%20%5Cfrac%7B2%7D%7B3x-2%7D%2B%5Cfrac%7B1%7D%7Bx%2B2%7D)